A new prescribed performance control approach for uncertain nonlinear dynamic systems via back-stepping. Issue 17 (November 2018) - Bu, Xiangwei; He, Guangjun; Wei, Daozhi
Abstract: Though traditional prescribed performance control (PPC) schemes can guarantee tracking errors with desired transient performance, they cannot ensure the convergence of tracking errors with small overshoot. In this study, we propose a novel PPC methodology for a class of uncertain nonlinear dynamic systems based on back-stepping, guaranteeing output tracking with small (even zero) overshoot. Firstly, new performance functions are constructed to constrain tracking errors. Then, to facilitate control designs, the "constrained" systems are transformed into equivalent "unconstrained" ones by designing a series of transformed errors. Furthermore, robust back-stepping controllers, requiring no priori knowledge of uncertainties' upper bounds, are developed utilizing transformed errors instead of initial tracking errors. Semi-globally uniformly bounded stability of the closed-loop control system is guaranteed via Lyapunov synthesis. Finally, simulation and experiment results are presented to verify the design.